Efficacy of Miniature Punch Grafting Followed by Puvasol Therapy in Refractory Stable Vitiligo - Anu Gupta; C Chaudhary; V Goyal; D Lal; SK Gupta (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Vitiligo affects approximately 2% of the worldwide population regardless of race, ethnic background or gender. When the medical methods are not successful, surgical procedures may be considered with the aim of placing a new source of pigment cells to reinitiate melanogenesis within the affected areas. This study was conducted to evaluate the efficacy of combining punch grafting followed by PUVASOL therapy in vitiligo patients. After punch grafting patients are given PUVA/PUVASOL exposure.